The influence of a deliberate practice intervention on the putting performance and subsequent practice behaviours of aspiring elite adolescent golfers - Hayman, R.; Polman, R.; Borkoles, E.; Taylor, J. (Talent Development & Excellence, 2013)
Objectives: This study aimed to determine if a golf specific deliberate practice intervention would improve putting performance and influence future practice behaviours of aspiring elite adolescent golfers with no prior experience of specialised short game interventions. Method: Participants completed a 13 week AB single - subject multiple - baseline design study with social validation and five month follow up interviews. Results: The findings indicated the deliberate practice intervention to be effective in enhancing the putting performance of all participants from baseline to intervention phases. Mean performance measure scores were significantly higher in the intervention phase than the baseline phase. Social validation and follow up interviews revealed all participants enjoyed undertaking deliberate practice, experienced a range of psychological and technical improvements, adapted current training schedules to mirror deliberate practice and committed long term to activities of this nature. Conclusions: Deliberate practice has the potential to improve putting performance of aspiring elite adolescent golfers and was viewed by all participants as a key strategy in successfully bridging the gap to elite adolescent status. Findings provide support for practitioners, sport psychologists and policy makers who may wish to expose aspiring elite golfers to golf specific deliberate practice regimes for the first time during late adolescence.